HUBUNGAN PENGETAHUAN DAN ASUPAN GIZI TERHADAP KEJADIAN KEK PADA IBU HAMIL DI KECAMATAN TERBANGGI BESAR KABUPATEN LAMPUNG TENGAH PROVINSI LAMPUNG - , Esther Adhiyati, Prof.dr.M. Hakimi, S.pOG. K, PhD ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: CED is a health problem commonly occurs in women and children. Data of Lampung Tengah District Health Office showed the prevalence of CED in pregnant mothers in 2007 was high, i.e. 20.03%. CED in pregnant mothers can affect birth weight and increase risk for mortality in mothers and children. Objective: To analyze association between knowledge of pregnant mothers and nutrition intake and the incidence of CED at Subdistrict of Terbanggi Besar, District of Lampung Tengah. Method: The study used cross sectional design. The research was conducted in the District Terbanggi Besar, Central Lampung regency. The study was conducted for 2 months, which will be held in September-November 2011. Subject of the study consisted of 122 pregnant mothers, comprising 61 with CED and 61 without CED. Data of CED were obtained from assessment of arm circumference of the subject compared to the normal standard of â¥ 23.5 cm. Data of knowledge on CED and nutrition were obtained from questionnaire. Data of nutrition intake were obtained from questionnaire and interview using food frequency questionnaire. Association between knowledge and nutrition intake of the subject and CED was analyzed using bivariate with chi square test. All statistical analyses were based on significance Î±=0.05 and CI 95%. Results & Discussion: The result of statistical test showed there was association between knowledge of pregnant mothers and nutrition status. Pregnant mothers with CED had lower knowledge than those without CED. There was association between energy and protein intake of pregnant mothers and the incidence of CED. Pregnant mothers with CED had lower energy and protein intake than those without CED. Conclusion: Knowledge and nutrition intake (energy and protein) in pregnant mothers were associated with the incidence of CED.